Addressing Professional Competency Problems in Clinical Psychology Trainees. (20th March 2017) - Nicholson Perry, Kathryn; Donovan, Mark; Knight, Rosalind; Shires, Alice
Abstract : Objective: Clinical psychology trainees with problems of professional competence (PPC) continue to be a challenge for courses. Despite the rapid development of competency‐based training models, the impact of this shift to the identification and management of professional competency problems is unclear. This project aims to describe how clinical psychology trainees with PPC are identified and managed within the Australian and New Zealand context. Method: An online survey was distributed through Australian and New Zealand universities offering clinical psychology training programmes. Questions addressed approaches to monitoring progress on placements, identification and management of trainees determined to be underperforming on placements, and the perceived usefulness of a range of strategies such as the use of standardised‐rating tools. Results: Thirty one responses were received, representing 40 clinical psychology training courses in 22 institutions across Australia and New Zealand. In all cases, at least one trainee with a PPC had been detected in the previous 5 years, most commonly attributed to psychological, behavioural, and developmental issues. Respondents reported the use of a range of preventive and remedial strategies, including the use of psychometrically validated competency evaluation rating forms to assist in the grading of placements. Conclusion: Trainees with PPC occur on a fairly regular basis in clinical psychology training courses in Australian and New Zealand. While some processes involved in the identification and management of these students have been refined and systematised, some opportunities to facilitate early identification and remediation may yet need further enhancement.